Tourism Village Service Readiness Through Life Skills - Susanto, Shobri Firman; Yusuf, Ali; Widyaswari, Monica (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
The readiness of tourism village services through life skills aims to make visiting tourists feel comfortable and minimize the potential for accidents. The special purpose of this research is to describe the methods used by the Lombok Kulon Organic Tourism Village Manager in acquiring life skills. This study uses a qualitative case study type approach. Interviews, observation, and documentation study carry out data collection methods. Data analysis is done repeatedly using data collection, data display, data reduction, and conclusion. The findings of the research on service skills readiness are carried out using 3 (three) methods, namely: (1) independent learning is carried out to deepen existing soft skills and hard skills, (2) bringing in experts is carried out to acquire new soft skills or hard skills, and (3) a comparative study is conducted to acquire soft skills and hard skills simultaneously.